Utilization of Solar Energy in Improving Energy Efficiency of Urban Households: A Bibliometric Review - Farida Arinie Soelistianto; Aris Triwiyatno; Bambang Winardi; Arnes Yuli Vandika (West Science Interdisciplinary Studies, 2024)
The utilization of solar energy has emerged as a critical solution for improving energy efficiency and achieving sustainability in urban households. This study conducts a bibliometric review to explore the research landscape on solar energy adoption, focusing on technological advancements, socio-economic implications, environmental benefits, and policy frameworks. The analysis identifies key themes such as photovoltaic innovations, smart grid integration, and energy storage technologies, as well as the influence of government incentives and community-based projects on adoption rates. While solar energy offers significant environmental and economic benefits, challenges such as high installation costs, energy variability, and aesthetic concerns remain. The findings highlight the need for interdisciplinary approaches and emerging technologies, including artificial intelligence and decentralized systems, to overcome these barriers. This review provides valuable insights for researchers, policymakers, and stakeholders to advance solar energy utilization and contribute to sustainable urban development.